(untitled) (Al-Nahrain Journal of Science, 2018)
The study was carried out to investigate humoral immune response in children infected with visceral leishmaniasis in Iraq at different stages of the disease IFAT detection of serum anti-leishmanial antibodies and measurement of total immunoglobulin level IgG, IgM, IgA and complement component C3, C4 as examples of humoral immune response throughout the infection. The results revealed that the IFAT test indicates useful applications of the technique for detection of Kala-azar infection, the titers of antibodies ranged 1/16-l/64 and were significantly correlated with the severity of infection, while serum mean levels of IgG, IgM were significantly increased during infection (1894.43 mg/dl and 145.16 mg/dl respectively) compared to that of healthy controls (942.8 mg/dl and 99.04 mg/dl respectively). No significant differences in the mean level of IgA in infected children in comparison to that of healthy control. The mean level of C3 was significantly less than that of the control group, while the mean serum level of C4 was significantly increased in the disease group compared lo that of the control group.